ANALISIS PEMANFAATAN TEKNOLOGI INFORMASI DAN PEMBERDAYAAN DALAM MENINGKATKAN PRODUKTIVITAS KERJA TENAGA KEPENDIDIKAN DI POLITEKNIK NEGERI MANADO - Efendy Rasjid; Mariska Walean; Reyners Tenges; Jemmry Winokan (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2021)
The Industrial Revolution 4.0 is marked by changes in the progress of science and technology that are so fast that it provides challenges for the world of educations to be able to manage Human Resources (HR)